2007
DOI: 10.1179/174329307x227247
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local heat treatment on residual stresses in electron beam welding

Abstract: Electron beam welding (EBW), as a high performance welding method, is also subject to requirements of high integrity welds which particularly include residual stresses affecting distortion and fatigue behaviour. In this context multiple beam technique may provide new applications of specific thermal weld treatment. The present work introduces a promising method of local post-heating in a certain distance to the current welding location applying multiple beams for the reduction in residual stresses in EB welded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Cowles et al [7] developed a three-dimensional (3D) model to predict the residual stress of EBW on a high-pressure drum rotor and compared the simulated results with an experiment using hole-drilling technology in which the thickness of the component for the 3D model was 8.89 mm. Rosen et al [8] investigated the appropriate parameters of local postheating by applying multiple electron beams using the FEM and experiments with strain gauges in which the thicknesses of welded plates are 2 mm and 3 mm. Lundba¨ck and Runnemalm [9] developed a 3D FE model to predict the distortion and residual stresses in two plates with 6-mm and 7-mm thickness during EBW, and the predictive residual stress was validated by experiment using an incremental holedrilling technique.…”
Section: Introductionmentioning
confidence: 99%
“…Cowles et al [7] developed a three-dimensional (3D) model to predict the residual stress of EBW on a high-pressure drum rotor and compared the simulated results with an experiment using hole-drilling technology in which the thickness of the component for the 3D model was 8.89 mm. Rosen et al [8] investigated the appropriate parameters of local postheating by applying multiple electron beams using the FEM and experiments with strain gauges in which the thicknesses of welded plates are 2 mm and 3 mm. Lundba¨ck and Runnemalm [9] developed a 3D FE model to predict the distortion and residual stresses in two plates with 6-mm and 7-mm thickness during EBW, and the predictive residual stress was validated by experiment using an incremental holedrilling technique.…”
Section: Introductionmentioning
confidence: 99%
“…This practice linked example verifies that this stress mitigating procedure provides a qualified tool for longitudinal stress mitigation in beam welds in complex components and weld geometries by drawing on the recommendations for the process parameter values which were reasoned in Ref. 17. As concerns the temperature the experimental results for the austenitic steel upgrade these recommendations by the fact that the most suitable temperature region to be generated in the heat treated zones depends on the temperature dependent material properties.…”
Section: Resultsmentioning
confidence: 94%
“…Kattoura et al [9] reported the extremely prosperous effect of laser peening method on reducing the residual stresses. Also, many other researchers have focused on similar techniques for improving the integrity of structures [10][11][12]. However, the time and price consuming are the well-known problems of these techniques which make them undesirable at the industrial applications, especially in repair welding and welding of large components.…”
Section: Introductionmentioning
confidence: 99%